Sistem Penjaminan Mutu Eksternal di SD Negeri Petompon 03 Semarang (Lembaga Pengembangan Kinerja Dosen, 2025)
This study analyzes the implementation of the External Quality Assurance System within the context of enhancing educational quality. Facing globalization challenges, quality education is crucial, yet significant obstacles like access disparities, teacher qualifications, and curriculum relevance persist. Consequently, robust education systems and quality assurance mechanisms are vital. This case study aims to elaborate on the concept of educational quality, outline EQAS mechanisms, and analyze its application at SD Negeri Petompon 03 Semarang, thereby providing comprehensive insights into quality assurance components and their operationalization. Employing a qualitative approach with a case study design, this research integrates both secondary data (regulatory documents, BAN-PDM accreditation data) and primary data (in-depth interviews with school and education agency stakeholders, observations, and internal document analysis). Qualitative data analysis involves reduction, presentation, and drawing conclusions verified through triangulation. Findings reveal that EQAS at SD Negeri Petompon 03 encompasses periodic evaluations by school supervisors and BAN-PDM. Although the school achieved a